2009
DOI: 10.1007/s11604-009-0320-9
|View full text |Cite
|
Sign up to set email alerts
|

Successful portal-systemic shunt occlusion of a direct shunt between the inferior mesenteric vein and inferior vena cava with balloon-occluded retrograde transvenous obliteration following recanalization after placing a covered stent in the portal and superior mesenteric veins

Abstract: Extrahepatic portal-systemic shunts cause portal-systemic encephalopathy. Direct communication between the inferior mesenteric vein (IMV) and the inferior vena cava (IVC) is a relatively rare pathway among the variety of portal-systemic shunts. This report describes a case of successful occlusion of an IMV-IVC shunt. Based on laboratory data and computed tomography findings, a 69-year-old woman with liver cirrhosis was diagnosed with portal-systemic encephalopathy due to a shunt between the IMV and the IVC. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…27,28 However, neither BRTO or PARTO can be performed if patients do not have a catheterizable gastrorenal shunt. 29,30 Furthermore, there are only a few scattered case reports on the use of BRTO for ectopic varices, [31][32][33][34][35][36] none of which include rectal varices. For these patients, PTVE can still be performed.…”
Section: Gastric Varicesmentioning
confidence: 99%
“…27,28 However, neither BRTO or PARTO can be performed if patients do not have a catheterizable gastrorenal shunt. 29,30 Furthermore, there are only a few scattered case reports on the use of BRTO for ectopic varices, [31][32][33][34][35][36] none of which include rectal varices. For these patients, PTVE can still be performed.…”
Section: Gastric Varicesmentioning
confidence: 99%
“…A portal vein hepatic vein shunt (PV shunt) in the liver is a relatively rare abnormality 1 , 2 that can cause hyperammonaemia and neurological symptoms. 2 4 Previous studies reported little success when using conventional treatment with interventional radiological strategies. 2 This is because the blood flow at the site of a PV shunt is rapid, and coils placed at the PV shunt sometimes migrate out of the target site.…”
mentioning
confidence: 99%